Case Report: Evidences of myasthenia and cerebellar atrophy in a chinese patient with novel compound heterozygous MSTO1 variants - Liu, Liqun; Su, Ruiting; Huang, Peng; Li, Xingfang; Xiong, Jie; Xiao, Yangyang; Mao, Dingan; Liu, Lingjuan (Frontiers in Genetics, 2022)
Misato Mitochondrial Distribution and Morphology Regulator 1 (MSTO1) is a soluble cytoplasmic protein that regulates mitochondrial dynamics by promoting mitochondrial fusion. Variants in the MSTO1 gene cause a rare disease characterized by early-onset myopathy and cerebellar ataxia, with almost 30 cases reported worldwide. Here we report a case of a 3-year-old boy with novel heterozygous variants of the MSTO1 gene (c.1A>G (p.M1?) and c.727G>C(p.Ala243Pro)). Sequencing data and subsequent validation show that the two variants were inherited from the mother and father of the patient (both were heterozygous). The clinical features are infancy-onset mental and motor retardation, language disorder, dysarthria, scoliosis, cerebellar atrophy, tremor, lower-extremity muscle weakness, elevated muscle enzymes, extensive myopathy with chronic atrophy, hyperventilation lungs, and previously unreported hairy back and enlarged gastrocnemius. Finally, novel heterozygous MSTO1 variants were discovered in this case, which expands the gene spectrum and clinical phenotype of this type of disease, and provides a new direction for future treatment and research. Then we summarize the mutational spectrum, pathological, clinical features and imaging of MSTO1 variants in a cohort of reported 31 patients and discuss the pathogenesis of MSTO1 in humans.